Emergency department triage performance timing. A regional multicenter descriptive study in Italy. (November 2016) - Bambi, Stefano; Ruggeri, Marco; Sansolino, Sandra; Gabellieri, Massimo; Tellini, Sabrina; Giusti, Monica; Ciulli, Elisa; Franchi, Federica; Petrocchi, Laura; Olivi, Mauro; Gravili, Raffaele Carlo; Biancalana, Paola; et al.
Highlights: The timing of emergency nurses' triage performance should be fast to ease the patients' workflow. This pragmatic study explores the time employed by nurses to perform the ED triage. Triage timing is influenced by nurses' experience, identity optical readers, and pediatric patients. Interruptions were recorded in 35.9% of triage processes. These results could be useful to set triage quality performance indicators. Abstract: Objectives: We explored the time employed by nurses to perform the ED triage process in the clinical setting. Moreover, we assessed the influences on triage timing performance exerted by variables related to nurses, local EDs' features, and by interruptions. Methods: This is a multicenter prospective descriptive-explorative study performed in 11 EDs of the Tuscany region (Italy), using a 5 tier triage system. The sample was made up of 1/3 of nurses working in each ED. Sampling was performed by a stratified proportional randomization (length of service classes: <5 years; 5–10 years; >10 years). Triage nurses were observed during their triage work-shift. Results: In 2014, 120 nurses were observed, during 1114 triage processes. The timings of triage phases were: waiting time to triage, median 2.55 min (IQR 1.28–5.03 min; range 0.1–56.25 min); triage duration, median 2.58 min (IQR 1.36–4.35 min; range 0.07–50 min). 400 interruptions were recorded (35.9%). In 9.9% there were 2 interruptions at least. There were significant differences in the medians of triage duration among the years of nurses' triage experience ( P < 0.001). The presence of interruption was significantly associated with the increasing of the time intervals in all the triage phases ( P < 0.0001). Finally, we recorded significant differences in all the triage time phases between the EDs. Conclusion: We found that the nurses triage time performances are similar to other triage systems in the world.